Gender-based structural violence in independent Algeria: A political strategy - Carmelo Pérez Beltrán (Feminismo/s, 2004)
This article deals with the concept of «structural gender violence», applied to the specific case of Algeria, according to the hypothesis that the Algerian State, practically since the independence of the country in 1962, has promoted an unequal development in order to repress women’s potential. The three areas covered in this study are education, work and politics. The conclusion is that the Algerian regime has established an aggressive political, ideological and economic system with the aim of excluding women from all areas of public life, in order to assign them a role confined to the private sphere of the traditional Algerian family.